CURRICULUM DEVELOPMENT ASSISTANCE FOR ENGLISH PROGRAM AT ATTARBIYATUL ISLAMIYAH BOARDING SCHOOL PROBOLINGGO - Tirmidi, Tirmidi; Soleh, Achmad Fathorrosi; Murtasiyah, Murtasiyah (Universitas Pahlawan Tuanku Tambusai, 2023)
In contrast to the highly important position of curriculum in teaching-learning process, English Program at Pesantren Attarbiyatul Islamiyah Paiton Probolinggo Islamic Boarding School has not yet had its curriculum document. This community service activity is intended to give assistance to the administrators of the Attarbiyatul Islamiyah Islamic Boarding School in compiling the English Language Program curriculum document. By using the curriculum development steps by Tyler and Taba, this activity will have output in the form of the curriculum document of English Program the Attarbiyatul Islamiyah Islamic Boarding School, which inclues: Statement of General Goals, Diagnosis of Needs, Formulation of Objectives, Selection of content, Organization of Content, Selection of Learning experience, Organization of learning Experience.